In vitro anti-aging activities of crocodile (Crocodylus siamensis) blood extracts - Jiradej Manosroi (2018)
© 2017, Chiang Mai University. All rights reserved. The objective of this study was to determine anti-aging activities of crocodile (Crocodylus siamensis) blood extracts. The extracts were prepared from the whole blood and the precipitated blood (in which the serum was separated). Each was extracted by six different processes including cold water (WC), hot water (WH), cold ethyl acetate (EC), hot ethyl acetate (EH), cold methanol (MC) and hot methanol (MH). The ethyl acetate and methanol extracts were dried by a hot air oven, while the water extracts and the seperated serum were by lyophilization. The total of 15 extracts was investigated for in vitro anti-aging activities including antioxidant, tyrosinase inhibition and gelatinolytic activity of MMP-2 inhibition on human skin fibroblasts as well as cytotoxicity. The dried blood serum (SR) gave the highest DPPH radical scavenging (SC 50 value = 1.83±0.60 mg/ml) and lipid peroxidation inhibition (IPC 50 value = 0.91±0.13 mg/ml). The precipitated blood extracted by cold ethyl acetate (POEC) showed the highest metal chelating (MC 50 = 0.0085±0.007 mg/ml). The tyrosinase inhibition activity of POEC (IC = 0.016±0.003 mg/ml) was higher than kojic acid of 2.25 times. All extracts gave no cytotoxicity at all concentrations except the blood extracted by cold water (CBWC) at 1 mg/ ml. The extract which indicated the highest cell viability at 1 mg/ml was the precipitated blood extracted by hot methanol (POMH). The blood extracted by cold ethyl acetate (CBEC) exhibited the highest MMP-2 inhibition activity on human skin fibroblasts with the percentages of pro MMP-2 inhibition at 47.30±10.51%, but lower activity than ascorbic acid of 1.93 times. The result from this study has demonstrated the commercial potential of crocodile blood to be developed as raw materials for an anti-aging product.